The Effects of Mission‐Oriented Public R & D Spending on Private Industry - CARMICHAEL, JEFFREY (Journal of Finance, 1981)
ABSTRACT This paper addresses the question of how government mission‐oriented R & D spending affects private R & D spending and thereby the total investment in technology. The problem is approached within the context of the capital asset pricing model in which the firm views investment projects in terms of their risk and return characteristics. The firm is assumed to produce jointly an established product and an R & D‐intensive product, where the latter generates an additional output of technology, or spillover, that is used as an input into the former. By investing in R & D the firm alters its risk and return characteristics in two ways: through the expected profits from the sale of the R & D‐intensive good; and through the expected profits from the spillover. In this model, government mission‐oriented R & D contracting affects the firm by enabling it to separate to some extent these two sources of risk and return. The main implication of the analysis is that while some public crowding out of private R & D is likely, this is almost certain to be incomplete. The empirical evidence from the U.S. transport industry supports the model and suggests that each dollar of government funding adds around 92 cents to total R & D spending; crowding out private investment by as little as eight percent.